Initial Value Problem for Stochastic Hyprid Hadamard Fractional Differential Equation: Hyprid Hadamard - El-Borai, Mahmoud Mohammed Mostafa; El-sayed, Wagdy G.; Badr, A. A.; Sayed, Ahmed Tarek (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, we discuss the existence of solutions for a stochastic initial value problem of Hyprid fractional dierential equations of Hadamard type given by where HD is the Hadamard fractional derivative, and is the Hadamard fractional integral and be such that are investigated. The fractional calculus and stochastic analysis techniques are used to obtain the required results.